“Desarrollar una APP con realidad aumentada para ilustrar de forma interactiva la flora y fauna del parque Nacional Cotopaxi” - Asanza Orozco, Carlos Javier (2024)
Tourism is an important source of income, and improving the tourist experience with technology is essential for its development. Cotopaxi National Park is known for its abundant biodiversity and natural beauty. However, the lack of innovative applications that employ emerging technologies such as augmented reality has hindered their efforts to promote tourism in a sustained way. To address this problem, it is proposed to develop an informative and entertaining mobile application that uses augmented reality, managing to provide an immersive and enriching experience for visitors of this natural reserve. The bibliographic review has allowed us to identify keys in the development of the mobile application, collect detailed information about the place, improving the tourist experience of the Cotopaxi National Park. The application is designed to illustrate interactively the flora and fauna of the place, using advanced technologies such as the Unity SDK, AR Foundation, Google's AR Core, and Vuforia, apart from providing essential information about this tourist destination for both, local and foreign tourists, ensuring that they are always informed. This project aims to take advantage of emerging technologies to improve the tourist experience in this reserve, offering the visitors a new and attractive experience to interact with the natural and cultural environment. This initiative aims to overcome physical limitations through a visionary strategy that promotes tourism and protects the valuable natural and cultural heritage of the destination place. This application redefines how tourist destinations can attract their audience, showing the transformative potential of technology in this sector.